A Review Study on Ashta Ksheera their Nutritional and Therapeutic Values in Children - Pathak, Vijay Kumar; Sharma, Pankaj; Mahapatra, Arun Kumar; Gupta, Prashant Kumar; Rajagopala , S (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Milk is a natural food source for mammals. Animals, including human, produce milk to feed their young until they are ready for solid food. Ayurveda identified eight different sources of animal milk under the name of Ashta Ksheera, of which human milk (Nari Dugdha) is also one; the other seven sources of milk are Avika (Sheep), Aja (Goat), Go (Cow), Mahishi (Buffallo), Ustra (Camel), Hasthini (Elephant), and Ashwi (Mare) milk. Objective: To review nutritional value of Ashta Ksheera in comparison to human milk supported with evidence-based research studies. Methods: Literature research of Ayurveda text and relevant studies depicting nutritional value and therapeutic value of Ashta Ksheera were searched, comprised an electronic database of Google scholar, PubMed, Ayush research portal and DHARA database. Results: Data from previous studies on Ashta Ksheera were extracted and compared its nutritional values with human milk (Nari Dugdha) and their properties described in Ayurveda. Discussion: Goat milk or sheep milk can be given to children allergic to cow milk. Cow milk acts as Rasayana (rejuvinating), Oja Vardhak (increasing immunity), it is best among the Jivaniya Padarthas (food enhancing life). Aja Dugha (Goat milk) is similar to Go dugdha (Cow milk) and can be use in Rajayakshma (emaciation like condition).